Eye Care Providers' Attitudes Towards Tele-ophthalmology - Woodward, Maria A. (Telemed J E Health, 2015)
Background: The rapid rise of e-health and remote care systems will likely change the practice patterns of ophthalmologists. Although telemedicine practices are thriving in many specialties of medicine, telemedicine for ophthalmology has been limited primarily to asynchronous care for diabetic retinopathy. The goal of this research was to evaluate perspectives on and familiarity with telemedicine among eye care providers at a large tertiary-care medical center via an anonymous, descriptive survey. Results: In total, 58 eye care physicians completed surveys (response rates of 86% for physicians-in-training and 49% for faculty physicians, respectively). Although a majority of both faculty and physicians-in-training were willing to participate in telemedicine services, trainees were more likely to be willing to interpret photographs than faculty (p=0.04). Most respondents (71%) indicated that they did not use telemedicine. Over half had received photographs (via phone or e-mail) for interpretation from referring physicians (54%) or patients (56%) within the past 3 months. A majority of providers (82%) would be willing to participate in telemedicine for consultations and for interpreting photographs, but a majority (59%) had low confidence in remote care for providing an opinion on patient care. Conclusions: Most eye care providers viewed telemedicine as part of the future of eye care but were concerned about the use of telemedicine. Although most providers did not practice telemedicine, over half of them were comfortable managing eye care consultations (including patients' photographs) via the Internet.